Correlation between Lithium Titanium Oxide Powder Morphology and High Rate Performance in Lithium-Ion Batteries - Hermes A. Llaín-Jiménez; Dominika A. Buchberger; Magdalena Winkowska-Struzik; Maciej Ratyński; Michał Krajewski; Maciej Boczar; Bartosz Hamankiewicz; Andrzej Czerwiński (Batteries, 2022)
This study determined the measurable factor responsible for the high rate performance of lithium titanium oxide (Li4Ti5O12, LTO) powders in lithium-ion batteries. The structural and morphological properties of various Li4Ti5O12 materials and their correlation with electrochemical performance were analysed. The results showed that there was a strong correlation between high capacity retention at 10 C and the specific surface area. Other electrochemical and structural factors, such as the crystal size and pore structure, were not correlated with 10 C performance. We found that an increase in the specific surface area of Li4Ti5O12 above c.a. 15 m2 g−1 neither improved the high rate capacity retention nor its specific discharge capacity at high current rates. We also showed that the sol–gel synthesized lithium titanium oxide powders could retain similar or higher discharge specific capacities than materials synthesized via more complex routes.